Post-treatment pain in teeth with primary infections - Jesus Djalma Pécora; Cynthia Rodrigues de Araújo Estrela; Orlando Aguirre Guedes; Aldo Brugnera Junior; Carlos Estrela (Faculdade São Leopoldo Mandic, 2008)
Objective: The purpose of this assay was to evaluate longitudinal studies about the pain after endodontic treatment, with primary infection, using a systematic review. Methods: A MEDLINE search strategy was developed to identify articles using the following uniterms: endodontic(s) and pulpal pain, endodontic(s) and periapical pain, endodontic(s) and symptom, endodontic(s) and flare-ups, endodontic(s) pain and post-treatment, endodontic(s) and inter-appointment/interappointment. The search included articles from the MEDLINE (http://www.ncbi.nlm.nih.gov/PubMed), from 1966 to 23rd February 2007. Results: 351 articles were selected (6 articles involved epidemiological studies, 16 were literature reviews; 55 case reports. Pain associated with apical limit was found in 10 articles; reference to irrigants solutions, 12 articles; to intracanal dressing, 29 articles; to root canal filling, 9 articles and to interappointment pain, 24 articles. Only 9 studies satisfied the inclusion criteria. Conclusion: From the studies evaluated, the estimated clinical success shows evidences that the sanitization process and rational use of intracanal medicaments lead to high rates of absence of post-treatment pain in primary endodontic infections.